Cytotoxicity of Ethanol Extract, Polar, Semipolar, and Nonpolar Herb Citolod (Isotoma longiflora (L.) C. Presl.) Cells on MCF-7 Cells - Haryoto, H; Hapsari, Atikah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Breast cancer is a major cancer suffered and the most cause of death by women in the world. The existing drugs of anticancer are not selective, disturbing the growth of normal cells. It encourages researchers to explore a chemopreventive agent from the nature materials. This study was conducted to determine the cytotoxic activity of ethanol extract, polar fractions, semipolar, and nonpolar herb chitolod (Isotoma longiflora (L) Presl.) on MCF-7 cells. First, herb chitolod was dried, refined, and sieved using mesh number 40 and then macerated using 96% ethanol for 72 hours. Phytochemical screening was conducted with TLC using GF254 silica as stationary phase, n-hexane: ethyl acetate (7: 3) as mobile phase, then the result was visualized on UV 254 nm, 366 nm, and visible light. Anisaldehid, dragendroff, sitoborat, and FeCl3 reagents spray were used as visualizer of TLC spot results. Fractination using KCV method, then cytotoxic test using MTT assay. A result obtained, the ethanol extract of herb chitolod positively contains flavonoids, phenolics, alkaloids, terpenoids, saponins, steroids and tannins. IC50 value of the ethanol extract, polar fractions, semipolar, and nonpolar are 521,05; 213,29; 499,94; and 239,43 µg/mL. This study showed that the ethanol extract, polar fraction, semipolar, and nonpolar of herb chitolod had moderate cytotoxic activity on MCF-7 cells.